Analysis of Factors Affecting Consumer Intention to Buy Honda Genio Motorcycles - Sugandha, Adita Primadana; Bella, Catresia Martha; Indarwati, Tias (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
This study aims to determine what factors influence consumer intentions to buy Honda Genio motorcycles. The author uses various sources, both research journals and from various books. In this study using an explanatory research design, this design is also called an exploratory design. The conclusion of this study is that consumers' purchase intentions are influenced by two main factors, namely product quality and brand image. Product quality is a consideration for consumers in making purchases because if consumers feel that they are suitable for Honda Genio and the product can meet their needs, then consumers make the decision to buy Honda Genio. Meanwhile, brand image is related to attitudes in the form of beliefs and preferences for a brand. Consumers who have a positive image of a brand are more likely to make a purchase.